PENGUKURAN KINERJA DENGAN MENGGUNAKAN KONSEP VALUE FOR MONEY PADA PEMERINTAH KAB. OKI SUMATERA SELATAN PERIODE 2017-2019 - Djenni Sasmita (JMB : Jurnal Manajemen dan Bisnis, 2020)
This study aims to determine the performance of the Regional Wealth and Financial Revenue Service (DPKAD) of Oki District, South Sumatra by using the concept of Value For Money. This research was conducted by collecting data for 3 years, from 2017 to 2019. This study used secondary data. The data analysis method used is descriptive qualitative analysis method. Based on the results of research using the concept of Value For Money based on 3 main elements, namely economy, efficiency and effectiveness, it shows that: Economic ratios get 86.54%, 82.64% and 71.43%, which means that the economic ratio is below 100% during 2017 -2019 and the results of this ratio indicate that the criteria for economic ratios are categorized as "economic". The efficiency ratio during the research year of this ratio was 94.69%, 105.17% and 97.95%, although in 2018 the ratio was less efficient because the percentage was above 100%. However, the performance of the Oki district government as a whole is included in the "efficient" category. Meanwhile, the ratio of effectiveness obtained is 96.53%, 86.65% and 76.98%, where the percentage ratio below 100% indicates that this ratio is considered "ineffective". Based on the research results, the concept of Value For Money is very well applied to Oki District DPKAD because it can provide a more structured and comprehensive picture of performance.